Chichibabin pyridinium synthesis. Issue 6 (7th February 2019) - Imura, Akiho; Tanaka, Nao; Usuki, Toyonobu
Graphical abstract: Highlights: Mechanistic studies of Chichibabin pyridinium synthesis were examined. Interesting pyridinium skeleton was formed under several conditions. GC–MS analysis of intermediate aldol condensate was carried out. Abstract: Chichibabin pyridine synthesis involves the reaction of three aldehydes and ammonia to form 2, 3, 5-trisubstituted pyridines. This study examined the synthesis of tetrasubstituted pyridinium from aldehydes and an amine hydrochloride in the presence/absence of Pr(OTf)3 . Important insights into the reaction mechanisms of Chichibabin pyridinium synthesis were proposed through the investigation of reaction intermediates along with quantitative GC–MS analysis.